A review on WO3 photocatalysis used for wastewater treatment and pesticide degradation - Yerkanat N. Kanafin; Alshyn Abduvalov; Marat Kaikanov; Stavros G. Poulopoulos; Timur Sh. Atabaev (Heliyon)
The rapid growth in the global population has led to increased environmental pollution and energy demands, exacerbating the issue of environmental contamination. This contamination is significantly impacted by various types of pesticides found in water sources, which pose serious health risks to humans, animals, and aquatic ecosystems. In response, extensive research into water treatment technologies has been conducted, focusing on efficient methods to remove these pollutants, with advanced oxidation processes and the utilization of tungsten trioxide (WO3) as a photocatalyst showing promising results. This paper aims to review WO3-based photocatalytic processes for pesticide degradation, highlighting the potential of modified WO3 structures to improve photocatalytic efficiency and address current environmental challenges. Different WO3 synthesis routes and methods for modification have been discussed. The synthesis of WO3-based photocatalysts encompasses various methods that significantly affect their morphologies, sizes, structures, and thus catalytic performance, cost-effectiveness, and environmental sustainability. Techniques like hydrothermal, solvothermal, co-precipitation, sol-gel, and green synthesis and physical deposition techniques are elaborated, highlighting their unique advantages in producing nanostructures with desired physical and chemical properties. Moreover, enhancement methods aimed at optimizing the photocatalytic activity of WO3 under visible light for pollutant degradation have been discussed. Evaluation of WO3-based photocatalytic systems for pesticide treatment, emphasizing the effectiveness of various catalysts in degrading pesticides including organochlorines, organophosphorus, and chloropyridines have been conducted.